Comfort in Floating : Taking Stock of Twenty Years of Freely-Floating Exchange Rate in Chile - Albagli, Elias (IMF Working Papers; Working Paper ;, 2020)
Chile offers an example of a country that has overcome the fear of floating by reducing balance sheet mismatches, enhancing financial market development, as well as improving monetary, fiscal, and political institutions, and strengthening policy credibility. Under the floating regime, Chile's economic adjustment to external shocks appears significantly improved, and its exchange rate pass-through has substantially declined. Our results reinforce the case that moving to a clear and credible floating regime can be associated with a reduction in the fear of floating via economic transformation (like smaller balance sheet mismatches, a larger hedging market, and a lower exchange rate pass-through).